Opportunities and gaps in conservation incentive programs on California agricultural land - Lenhardt, Julia; Egoh, B. N. (Frontiers in Sustainable Food Systems, 2023)
Agricultural incentive programs promote ecosystem health and biodiversity on California working lands and encourage a multitude of conservation goals. The various objectives, environmental impacts, and financial costs of conservation incentive programs are challenging to assess. The ecosystem services framework is a useful tool for identifying tradeoffs between conservation management options. Here, 52 active incentive programs were reviewed to determine the ecosystem services prioritized by each program in California. Next, the top 20 highest funded federal conservation practices were assessed in terms of their ecosystem service impacts. We found that there is a gap between California’s ecosystem services goals and the ecosystem services that are impacted by federal programs, and that the top funded practices are not necessarily the ones that deliver the best benefits in terms of ecosystem services. This study highlights the gaps between conservation goals and outcomes on California agricultural land, as well as the need for regional conservation monitoring to determine the impacts of incentive programs.